2022
DOI: 10.1055/a-1785-3936
|View full text |Cite
|
Sign up to set email alerts
|

A New Intranasal Influenza Vector-Based Vaccine TB/FLU-04L Against Tuberculosis: Preclinical Safety Studies

Abstract: A recombinant vector vaccine TB/FLU-04L for the prevention of tuberculosis was developed in RIBSP CS MES RK and SRII. The vaccine is based on the attenuated influenza strain Flu NS106/ESAT-6_Ag85A expressing mycobacterial antigens Esat-6 and Ag85A. This research aimed to conduct pre-clinical safety studies of the vaccine as one of the basic and mandatory stages in the development and introduction of immunobiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
(9 reference statements)
1
10
0
Order By: Relevance
“…The obtained vector demonstrated high replicative activity up to 8.0 lg TCID 50 /mL and was confirmed to be genetically stable after 15 consequent passages in Vero cells. The safety of TB/FLU-04L was proven in mice, guinea pigs, ferrets [ 38 ], and monkeys. There was no viral shedding detected in any animal model; the vaccine strain was completely attenuated in comparison with the wt A/PR/8/34 virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained vector demonstrated high replicative activity up to 8.0 lg TCID 50 /mL and was confirmed to be genetically stable after 15 consequent passages in Vero cells. The safety of TB/FLU-04L was proven in mice, guinea pigs, ferrets [ 38 ], and monkeys. There was no viral shedding detected in any animal model; the vaccine strain was completely attenuated in comparison with the wt A/PR/8/34 virus.…”
Section: Discussionmentioning
confidence: 99%
“…There was no viral shedding detected in any animal model; the vaccine strain was completely attenuated in comparison with the wt A/PR/8/34 virus. Toxicology studies revealed no toxicological or allergological effects of the vaccine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has issued recommendations that each country should develop its own vaccines and expand their vaccine production capacities. Over the past several years, the Scientific Research Institute for Biological Safety Problems (RIBSP) has been doing re-search to develop vaccines against influenza and M. tuberculosis for the Ministry of Health of the Republic of Kazakhstan [ 43 , 44 , 45 , 46 ]. Like many other countries, Kazakhstan started designing its own SARS-CoV-2 vaccine immediately after the COVID-19 outbreak with several candidate vaccines proposed by the RIBSP [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of T- cell stimulating adjuvants are AS01 E (adjuvant system 01 E ) and ISCOM (immune stimulating complex) based adjuvants ( 23 25 ). Alternatively, recombinant viral vectors expressing vaccine antigen(s) have been generated, which are mostly replication-deficient ( 27 31 ). The recently licensed Ebola vaccination scheme is based on a prime/boost scheme comprising adenovirus (Ad) 26 and Modified Vaccinia Ankara (MVA) virus as vectors, both expressing Ebola antigen ( 32 ).…”
Section: Major Vaccine Platformsmentioning
confidence: 99%